“Reality” of near-death-experience memories: evidence from a psychodynamic and electrophysiological integrated study - Palmieri, Arianna; Calvo, Vincenzo; Kleinbub, Johann R.; Meconi, Federica; Marangoni, Matteo; Barilaro, Paolo; Broggio, Alice; Sambin, Marco; Sessa, Paola (Frontiers in Human Neuroscience, 2014)
The nature of near-death experiences (NDEs) is largely unknown but recent evidence suggests the intriguing possibility that NDEs may refer to actually “perceived”, and stored, experiences (although not necessarily in relation to the external physical world). We adopted an integrated approach involving a hypnosis-based clinical protocol to improve recall and decrease memory inaccuracy together with Electroencephalography (EEG) recording in order to investigate the characteristics of NDE memories and their neural markers compared to memories of both real and imagined events. We included 10 participants with NDEs, defined by the Greyson NDE scale, and 10 control subjects without NDE. Memories were assessed using the Memory Characteristics Questionnaire. Our hypnosis-based protocol increased the amount of details in the recall of all kind of memories considered (NDE, real, and imagined events). Findings showed that NDE memories were similar to real memories in terms of detail richness, self-referential, and emotional information. Moreover, NDE memories were significantly different from memories of imagined events. The pattern of EEG results indicated that real memories recall was positively associated with two memory-related frequency bands, i.e., high alpha and gamma. NDE memories were linked with theta band, a well-known marker of episodic memory. The recall of NDE memories was also related to delta band, which indexes processes such as the recollection of the past, as well as trance states, hallucinations, and other related portals to transpersonal experience. It is notable that the EEG pattern of correlations for NDE memories recall differed from the pattern for memories of imagined events. In conclusion, our findings suggest that, at a phenomenological level, NDE memories cannot be considered equivalent to imagined memories, and at a neural level, NDE memories are stored as episodic memories of events experienced in a peculiar state of consciousness.